2015
DOI: 10.1021/acsnano.5b01426
|View full text |Cite
|
Sign up to set email alerts
|

Protection and Delivery of Anthelmintic Protein Cry5B to Nematodes Using Mesoporous Silicon Particles

Abstract: The ability of nano- and microparticles of partially oxidized mesoporous silicon (pSi) to sequester, protect, and deliver the anthelmintic pore-forming protein Cry5B to nematodes is assessed in vitro and in vivo. Thermally oxidized pSi particles are stable under gastric conditions and show relatively low toxicity to nematodes. Fluorescence images of rhodamine-labeled pSi particles within the nematodes Caenorhabditis elegans and Ancylostoma ceylanicum show that ingestion is dependent on particle size: particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 63 publications
5
35
1
Order By: Relevance
“…Cry5B in IBaCC showed a dose-dependent inhibition of motility similar to previously published studies with purified Cry5B (30). We had previously confirmed uptake of 0.4 µm particles by adult hookworms (56). To confirm uptake of IBaCC by hookworms, we labeled IBaCC with rhodamine, which predominantly labels full length Cry5B.…”
Section: Ibacc Is An Active Nematicidesupporting
confidence: 83%
“…Cry5B in IBaCC showed a dose-dependent inhibition of motility similar to previously published studies with purified Cry5B (30). We had previously confirmed uptake of 0.4 µm particles by adult hookworms (56). To confirm uptake of IBaCC by hookworms, we labeled IBaCC with rhodamine, which predominantly labels full length Cry5B.…”
Section: Ibacc Is An Active Nematicidesupporting
confidence: 83%
“…Since >99.9% of Cry5B is rapidly degraded in stomach acid ( Hu et al, 2010a ), we hypothesized that protection from stomach acid should improve efficacy. Previous attempts to protect Cry5B from stomach acid using nanoparticles failed, likely due to slow release kinetics ( Wu et al, 2015 ). To circumvent the challenges with formulation strategies, we tested whether direct inhibition of stomach acid proteolysis would improve Cry5B efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption kinetics study indicated that the adsorption of protein was gradually increased, then approached the adsorption equilibrium after around 2 h. This means that the adsorption could be regulated in a short time in the practical application of nano-Mg(OH) 2 as an adsorbent. Previous study also loaded the crystal protein anthelmintic Cry5B with partially oxidized mesoporous silicon (pSi), and the loading time was 16 h [ 17 ]. In our system, the adsorption of Cry11Aa by nano-Mg(OH) 2 was a rapid process, and the adsorption capacity could achieve equilibrium in the first 2 h. This excellent adsorption ability might be attributed to the large adsorption affinity of nano-Mg(OH) 2 and the relatively high BET areas.…”
Section: Discussionmentioning
confidence: 99%